Taxonomic, nomenclatural, and distribution notes on Thymus dreatensis (Nepetoideae, Lamiaceae) and related taxa endemic to North Africa - Mokni, Ridha El; Domina, Gianniantonio (Phytotaxa, 2024)
Thymus dreatensis (Lamiaceae), a rare species, was considered to be strictly endemic to Algeria, until it was recently discovered on the eastern Kroumirian mountains of Tunisia. The species is one of the very rare and few taxa of Thymus sect. Serpyllum subsect. Insulares and is characterized mainly by its small habit with reptant stems, broadly ovate to elliptical, entire leaf blade, and a capitate to oblong inflorescence with entire bracts, which are different from the leaves. The name is here lectotypified with a specimen housed in the Montpellier University Herbarium. The population is here reported for the first time as a new floristic record for Tunisia. Moreover, geographical distribution and habitat of T. dreatensis is given. In addition, the nomenclature of three species of Thymus that are morphologically close to T. dreatensis and endemic to North Africa, is discussed: T. atlanticus is lectotypified with a specimen housed in Herb. K; T. guyonii is neotypified with a specimen housed in Herb. P; T. pallescens is lectotypified with the same detailed plate on which the name was published.